Answer :
Answer:
y⁻⁷
Explanation:
Before we begin, remember the following rule:
1- mᵃ * mᵇ = mᵃ⁺ᵇ
2- mᵃ / mᵇ = mᵃ⁻ᵇ
Now, for the given we have:
y⁻⁹ * y⁻⁸ * y¹⁰
We can note that we are multiplying variables of same base with different powers. Therefore we will simply apply the first rule mentioned above and add the powers as follows:
y⁻⁹ * y⁻⁸ * y¹⁰ = y⁻⁹⁺⁽⁻⁸⁾⁺¹⁰
= y⁻⁷
Hope this helps :)
y⁻⁷
Explanation:
Before we begin, remember the following rule:
1- mᵃ * mᵇ = mᵃ⁺ᵇ
2- mᵃ / mᵇ = mᵃ⁻ᵇ
Now, for the given we have:
y⁻⁹ * y⁻⁸ * y¹⁰
We can note that we are multiplying variables of same base with different powers. Therefore we will simply apply the first rule mentioned above and add the powers as follows:
y⁻⁹ * y⁻⁸ * y¹⁰ = y⁻⁹⁺⁽⁻⁸⁾⁺¹⁰
= y⁻⁷
Hope this helps :)